Positive Impact of Lockdown due to COVID-19 on Pollution - Shah, Nita H.; Jayswal, Ekta N.; Suthar, Ankush H. (Discontinuity, Nonlinearity, and Complexity, 2026)
The outbreak of novel coronavirus disease, namely COVID-19, has become an international public health problem in a very short period. To control the dispersal of the disease from its source, mostly all countries have restricted transportation activities as well as lockdown is implemented. This study intended to explore the effects of travel restrictions due to the outbreak of COVID-19 on air pollution. In the present work, a mathematical model has been created using two compartments lockdown and pollution. Equilibrium point and its boundedness is shown with detailed computations. The main output is computed through basic reproduction number called threshold value. With sufficient conditions, local and global stability of equilibrium points convey attention to dynamical behaviour of model. Backward bifurcation has been conducted with reference of basic reproduction number. The main objective of paper is to reduce pollution by applying optimal control strategy on lockdown. Numerical simulation and sensitivity analysis lead more light on obtained analytically results.